PENGAWASAN PEMERINTAH DAERAH TERHADAP PENCEMARAN LIMBAH INDUSTRI BATIK DI KOTA PEKALONGAN PADA TAHUN 2010-2014 - Iys Syabilla Rusda; Purwoko Purwoko; Nunik Retno H (Journal of Politic and Government Studies, 2015)
The increasing pace of economic growth in Pekalongan and magnitude output of batik textile sector in particular, both small-scale industry and households, making batik industrial waste problems also increased. While the ability of waste management in the City of Pekalongan both by governments and entrepreneurs still lacking. This has caused rivers in the city of Pekalongan become contaminated.This research aims to (1) To be able to express and find out the control done by Local Government to the Batik waste contamination in the city of Pekalongan in 2010-2014. (2) To determine the extent of the control of the Local Government of the batik industrial waste contamination in Pekalongan in 2010-2014.This research is the descriptive research with the qualitative approach. The methods of collecting data in this research use interview, observation, and documentation. The data’s analysis uses the descriptive analysis to describe the situation in the research obviously without any manipulation.The research found there are two methods of control carried out by the Local Government of Pekalongan which in this case is the Environment Agency Pekalongan, namely preventive control and repressive control. The preventive control has done well although there are still shortcomings. Eg dissemination activities provided by the Environment Agency ofPekalongan that have not been thoroughly until the entire businessman batik in Pekalongan, so there is still a lack of awareness or participation from batik entrepreneur in minimizing batik industrial waste contamination. Whilethe repressive control conducted by the Environment Agency of Pekalongan, for the period 2010-2014 is the Environment Agency of Pekalongan not apply criminal sanctions to companies or batik entrepreneurs because these problems can be solved by either the company or batik entrepreneur with the Environment Agency ofPekalongan.Key words: Control, Batik Industrial Waste